A review on non-thermal plasma treatment of water contaminated with antibiotics - Magureanu, M.; Bilea, F.; Bradu, C.; Hong, D. (Journal of hazardous materials, 2021)
Large amounts of antibiotics are produced and consumed worldwide, while wastewater treatment is still rather inefficient, leading to considerable water contamination. Concentrations of antibiotics in the environment are often sufficiently high to exert a selective pressure on bacteria of clinical importance that increases the prevalence of resistance. Since the drastic reduction in the use of antibiotics is not envisaged, efforts to reduce their input into the environment by improving treatment of contaminated wastewater is essential to limit uncontrollable spread of antibiotic resistance. This paper reviews recent progress on the use of non-thermal plasma for the degradation of antibiotics in water. The target compounds removal, the energy efficiency and the mineralization are analyzed as a function of discharge configuration and the most important experimental parameters. Various ways to improve the plasma process efficiency are addressed. Based on the identified reaction intermediates, degradation pathways are proposed for various classes of antibiotics and the degradation mechanisms of these chemicals under plasma conditions are discussed. [Display omitted] •The potential of non-thermal plasma to degrade antibiotics in water is undeniable.•The key performance indicators are removal, mineralization and energy efficiency.•The energy cost of plasma treatment remains one of the greatest challenges.•Identified intermediate products reveal a variety of degradation pathways.•The safety of the treated effluent should be studied in more detail.